The Potential Synergic Effect of a Complex Pattern of Multiple Inherited Genetic Variants as a Pathogenic Factor for Ovarian Dysgenesis: A Case Report - Cattoni, Alessandro; Spano, Alice; Tulone, Anna; Boneschi, Annalisa; Masera, Nicoletta; Maitz, Silvia; Di Blasio, Anna Maria; Persani, Luca; Guizzardi, Fabiana; Rossetti, Raffaella (Frontiers in Endocrinology, 2020)
Non-syndromic primary ovarian insufficiency due to ovarian dysgenesis in 46,XX patients is an uncommon finding in the general population, even though several monogenic variants have been reported as causative factors. Here, we describe a 15-year-old patient diagnosed with gonadal dysgenesis possibly due to the interaction of three potentially pathogenic variants of genes involved in ovarian maturation, namely factor in the germline alpha (FIGLA), newborn ovary homeobox-encoding (NOBOX) and nuclear receptor subfamily 5 group A member 1 (NR5A1). We also describe a different degree of residual ovarian function within the proband's family, whose female members carry one to three demonstrated variations in the aforementioned genes in a clinical spectrum potentially dependent on the number of alleles involved. Our results support the hypothesis that the severity of the clinical picture of the proband, resulting in complete ovarian dysgenesis, may be due to a synergic detrimental effect of inherited genetic variants.